Czech.Math.J. 2017
DOI: 10.21136/cmj.2017.0446-16
|View full text |Cite
|
Sign up to set email alerts
|

On the intersection graph of a finite group

Abstract: Institute of Mathematics of the Czech Academy of Sciences provides access to digitized documents strictly for personal use. Each copy of any part of this document must contain these Terms of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The number of edges in a graph that intersect a vertex, or degree, is shown by the symbol 𝑑 𝐺 (π‘₯) [17]. Any graph where 𝑑 Ξ“ (π‘₯) = 𝑑 Ξ“ for any π‘₯, 𝑦 ∈ Ξ“(𝑉) is said to be regular [7] . If two unique vertex pairs x and y exist in a graph, the path between them is defined as a sequence of vertex pairs π‘₯ = 𝑦 0 , 𝑦 1 , … , 𝑦 𝑛 = 𝑦 such that(𝑦 𝑖 , 𝑦 𝑖+1 ) ∈ 𝐸(Ξ“) for 0 ≀ 𝑖 ≀ 𝑛 βˆ’ 1, and n is referred to as the length of this path [7] .…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of edges in a graph that intersect a vertex, or degree, is shown by the symbol 𝑑 𝐺 (π‘₯) [17]. Any graph where 𝑑 Ξ“ (π‘₯) = 𝑑 Ξ“ for any π‘₯, 𝑦 ∈ Ξ“(𝑉) is said to be regular [7] . If two unique vertex pairs x and y exist in a graph, the path between them is defined as a sequence of vertex pairs π‘₯ = 𝑦 0 , 𝑦 1 , … , 𝑦 𝑛 = 𝑦 such that(𝑦 𝑖 , 𝑦 𝑖+1 ) ∈ 𝐸(Ξ“) for 0 ≀ 𝑖 ≀ 𝑛 βˆ’ 1, and n is referred to as the length of this path [7] .…”
Section: Preliminariesmentioning
confidence: 99%
“…On the Cayley graph, many intriguing outcomes have been found see [2][3][4][5][6]. The intersection graph of a finite group G, denoted as 𝛽(G), is an undirected graph whose vertices are all nontrivial proper subgroups of G and whose two different vertices H and K are close when H ∩ Kβ‰  1 [7] . The independence graph of a finite groups is a graph whose vertices are the components G and where two vertices, x and y, are adjacent if there is a minimal generating set of G that includes x and y [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tamizh et al [31], continued the seminal paper of CsΓ‘kΓ‘ny and PollΓ‘k to introduce the subgroup intersection graph of a finite group G. Further, in [25], it was shown that the diameter of intersection graph of a finite non-abelian simple group has an upper bound 28. Shahsavari et al [29] have studied the structure of the automorphism group of this graph. The intersection graph on cyclic subgroups of a group has been studied in [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ma [12] reduced this upper bound to 28 in 2016. In the other direction, Shasavari and Khosravi [13,Theorem 3.7] proved in 2017 that diam(βˆ† G ) 3.…”
Section: Introductionmentioning
confidence: 99%